Improving Job Satisfaction Employee At Panti Waluya Sawahan Hospital Malang - Ifa Pannya Sakti; Nyoman Anita Damayanti; Thinni Nurul Rohmah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Customer satisfaction is related to the performance of employees, and employee performance is closely related to employee job satisfaction. The purpose of this study is to determine the effect of employee job satisfaction on patient satisfaction at the Panti Waluya Sawahan Hospital in Malang. The research method is to conduct a study on secondary data on employee job satisfaction from the results of the survey using a questionnaire to all employees, as many as 507 people in October 2019. The study of the survey results shows that the percentage of employees who said they were satisfied in the 6 aspects of employee job satisfaction was the lowest satisfied with the solution to complaints and most satisfied with the training opportunity. To increase employee job satisfaction, training activities, organizational culture, and self-efficacy should be improved